2010
DOI: 10.1007/s11693-010-9056-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermobifida fusca exoglucanase Cel6B is incompatible with the cellulosomal mode in contrast to endoglucanase Cel6A

Abstract: Cellulosomes are efficient cellulose-degradation systems produced by selected anaerobic bacteria. This multi-enzyme complex is assembled from a group of cellulases attached to a protein scaffold termed scaffoldin, mediated by a high-affinity protein-protein interaction between the enzyme-borne dockerin module and the cohesin module of the scaffoldin. The enzymatic complex is attached as a whole to the cellulosic substrate via a cellulose-binding module (CBM) on the scaffoldin subunit. In previous works, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…Interestingly, members of the family-6 glycoside hydrolase enzymes have never been found to be part of any known cellulosome system. However, endocellulase Tfu_1074 (Cel6A) was demonstrated to confer enhanced cellulose-degrading activity in simple designer cellulosomes (38,53). In contrast, Tfu_0620 (Cel6B) is an exoglucanase, which was shown to cause an antiproximity effect in designer cellulosomes, and was therefore deemed incompatible with the cellulosomal mode (38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, members of the family-6 glycoside hydrolase enzymes have never been found to be part of any known cellulosome system. However, endocellulase Tfu_1074 (Cel6A) was demonstrated to confer enhanced cellulose-degrading activity in simple designer cellulosomes (38,53). In contrast, Tfu_0620 (Cel6B) is an exoglucanase, which was shown to cause an antiproximity effect in designer cellulosomes, and was therefore deemed incompatible with the cellulosomal mode (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, endocellulase Tfu_1074 (Cel6A) was demonstrated to confer enhanced cellulose-degrading activity in simple designer cellulosomes (38,53). In contrast, Tfu_0620 (Cel6B) is an exoglucanase, which was shown to cause an antiproximity effect in designer cellulosomes, and was therefore deemed incompatible with the cellulosomal mode (38). Therefore, in this study, we chose to work with the well-characterized family-48 exocellulase Cel48A, with GH family-48 enzymes being a major component in the natural secreted cellulosomes (54-57) together with the family-5 endocellulase Cel5A, whose synergistic effect with Cel48A has been demonstrated previously and which were extensively used in their dockerin-bearing chimeric forms as successful components of designer cellulosomes (20-22, 37, 58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, we have chosen to study two LPMOs from the bacterium T. fusca, because our group has already performed the cellulosomal conversion of a dozen biomass-degrading enzymes from this model organism (21,27,30,31). The LPMOs E7 and E8 were initially described in an earlier study (32) but were then considered to be CBMs able of slightly enhancing the activity of other T. fusca cellulases, because their classification as LPMOs was not yet evident.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, obtaining a functional chimeric enzyme does not necessarily warrant that it will be beneficial when incorporated into a cellulosome complex. For instance, our group reported that the exoglucanase Cel6B from T. fusca could be successfully converted to the cellulosome mode but, upon insertion in a complex, would cause a strong antiproximity effect (31).…”
Section: Discussionmentioning
confidence: 99%